Bits and bytes of financial regulation - Algarvio, Diogo João Azevedo (2018)
Since 2008, banks have spent more than €342 billion on settlements, enforcement actions, and fines, and until 2020 according to Reuters this value is expected to rise to €400 billion. As a result, technological solutions were implemented to help Financial Institutions deal with the increasing compliance burden and regulators addressing the constant difficulties of enforcing and monitoring regulatory requirements to limit risks and promote financial stability. This led to the emergence of a whole new movement in the Financial Industry - Regulatory Technology. In this dissertation, the aim is to analyze how technology can help Financial Institutions deal with risky behavior and regulatory demands in the most efficient and cost-effective way and to show how extremely complex this process can be, by following the deployment of an electronic communications surveillance tool within a top-tier firm. Electronic communications are crucial parts of investigations such as the subprime mortgage crisis, the London Interbank Offered Rate and the currency market manipulation scandals or the COMEX gold and silver futures markets spoofing scandal. To appropriately address the nature of these threats, holistic risk assessment tools that gather these records (e-mail, chat, voice, trade logs, etc.), discover correlations and provide a credible output that necessitates supervisory review are of extreme importance. The challenge for Front-Office Supervisors is finding the proverbial “needle in a haystack” – the combination of Email, Chats, transactions records, voice logs, and other reports – that should be flagged for suspicious activity and reviewed in conjunction with Compliance and Anti-Fraud teams.